2008
DOI: 10.1073/pnas.0711878105
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning depends on perceptual constancy

Abstract: Perceptual learning refers to experience-induced improvements in the pick-up of information. Perceptual constancy describes the fact that, despite variable sensory input, perceptual representations typically correspond to stable properties of objects. Here, we show evidence of a strong link between perceptual learning and perceptual constancy: Perceptual learning depends on constancybased perceptual representations. Perceptual learning may involve changes in early sensory analyzers, but such changes may in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
(46 reference statements)
1
42
0
1
Order By: Relevance
“…Emphasis on the discovery of invariance amidst robust variation is crucial in realistic learning tasks, but it differs from most contemporary laboratory studies of PL, which typically target simple sensory discriminations and involve large numbers of trials with a small set of fixed stimuli (e.g. Fahle & Poggio, 2002; for a discussion, see Garrigan & Kellman, 2008). Finally, PL interventions tend to have m inimal emphasis on explicit instruction.…”
Section: Elements Of Perceptual Learning In Instructionmentioning
confidence: 96%
See 3 more Smart Citations
“…Emphasis on the discovery of invariance amidst robust variation is crucial in realistic learning tasks, but it differs from most contemporary laboratory studies of PL, which typically target simple sensory discriminations and involve large numbers of trials with a small set of fixed stimuli (e.g. Fahle & Poggio, 2002; for a discussion, see Garrigan & Kellman, 2008). Finally, PL interventions tend to have m inimal emphasis on explicit instruction.…”
Section: Elements Of Perceptual Learning In Instructionmentioning
confidence: 96%
“…As we have seen, selective computation of abstract properties, from simple ones such as edge orientation in space, to more complex ones such as shape or sets of motion relationships that specify objects, surfaces or events, is a fundamental characteristic of perception ( J. Gibson, 1979) and appears to be presumed by learning mechanisms as well (Garrigan & Kellman, 2008). …”
Section: The Selective Character Of Perceptionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, Garrigan & Kellman (2008) have found that high-level perceptual constancy rather than low-level sensory constancy is crucial for learning. Zhang et al (2008) have found that top-down segregating cues ('tagging') allowed the perceptual system to dissociate between similar, sequentially presented inputs and hence to improve contrast discrimination.…”
Section: Perceptual Learning (A)mentioning
confidence: 99%